MANAJEMEN PEMBELAJARAN BAHASA INGGRIS PADA SMAN 3 BATUSANGKAR - Ade Alfa Pramudia (al-fikrah: Jurnal Manajemen Pendidikan, 2018)
The problem of this research was that the English instructional management at SMAN 3 Batusangkar has unrevealed yet. The purpose of this research was to describe the English instructional management at SMAN 3 Batusangkar. The researcher used case study of qualitative research. In analyzing the data, researcher used Miles and Huberman steps, they are data reduction, data display, and conclusion drawing/verification. In checking data trustworthyness, the researcher used data triangualtion technique. Based on the result of this study, it can be concluded that concluded that English instructional management at SMAN 3 Batusangkar is in compliance as mandated in the regulation. It can be seen through intracurricular aspects,  such as  in planning, using method, conducting learning activities, and doing evaluation, and at extracurricular aspects,  such as motivating student, rebuilding emotional relationship, practicing English, and channeling the students’ English talent, in spite of  weaknesses  in implementing innovative learning methodologies by the teachers.